O Estado como promotor do desenvolvimento artístico-cultural: pesquisa-ação no Centro Cultural Teatro Guaíra - Dias, Agemir de Carvalho (2014)
The research aims to analyze the role of the state as promoter of artistic and cultural development through a case study. The object of study is Cultural Center Guaíra Theater (CCTG), an agency of State of Paraná created by Law No. 9663/1991. The CCTG is currently responsible for directing Guaíra Theater, José Maria Santos Theater, Paraná Symphony Orchestra, Dance School, Guaíra Theater Ballet, G2 Dance Company. The problem to be analyzed is the role of CCTG, as stated in its charter, as promoter of the artistic and cultural development in the state of Paraná in a situation of state financing difficulties, the market competition with the end of their practically cultural monopoly in the field of theatrical performances in the city of Curitiba, and the lack of staff renewal of their bodies stable. The working hypothesis is that the CCTG runs the risk of becoming an institution anachronistic in its purpose of promoting culture in the face of changing conditions imposed by a new modernity. The methodology to be used is based in the action research on the analysis of documents produced by the Cultural Center Guaíra Theater and databases available through Transparency portals of government of the State of Paraná. The main conclusion is that the CCTG faces difficulty in executing their statutory objectives by difficulties in management of human, financial and artistic resources in some projects. It is proposed the management of CCTG by a Social Organization (OS) transforming the state bureaucratic management for more efficient management.